STEAM-ECE: Developing a STEAM Approach for Early Childhood Education in Indonesia - Louise Kay; Suci Putri; Finita Dewi; Alison Buxton; Tia Buyani (Indonesian Journal of Early Childhood Education Studies, 2025)
This paper examines the introduction of STEAM (Science, Technology, Engineering, Arts, and Mathematics) education in Early Childhood Education (ECE) in Indonesia, focusing on the 2022 Merdeka Curriculum's (MoECRT, 2022) efforts to incorporate technology and digital literacy into learning. Despite some progress, teachers still face challenges implementing STEAM into their teaching practice due to a lack of confidence and resources. The study explores the STEAM-ECE project, a capacity-building initiative led by MakerFutures and universities in the UK and Indonesia, designed to empower pre- and in-service teachers and ECE lecturers with the skills and knowledge to implement STEAM learning. The project included hands-on workshops, where teachers gained skills and confidence in making and implementing a maker approach in their classrooms. Interviews were carried out with seven teachers and six ECE university lecturers who had attended the workshop and had implemented the sessions into their own practice. These interviews aimed to explore the workshop’s impact on teaching practice and how the ECE lecturers had assimilated the workshop content into their pre-service curriculum. The findings emphasize the importance of local expertise in sustaining STEAM education and highlight the potential of makerspaces as innovative learning environments. This study contributes new insights into STEAM implementation in ECE within Low- and Middle-Income Countries, offering a scalable professional development model adaptable to diverse cultural contexts.